DETEKSI KADAR KARBON MONOKSIDA PADA KENDARAAN BERMOTOR MENGGUNAKAN ESP8266 - Bahrun Niam; Martselani Adias Sabara; Ulil Albab; Muchamad Sobri Sungkar; Rony Darpono; Qirom Qirom; Dany Sucipto (CV. Denasya Smart Publisher, 2025)
One of the sources of air pollution is motor vehicle exhaust, the gas produced from fuel combustion occurs in vehicle engines and also because the incomplete combustion process can have a negative impact on health and the environment. To reduce the impact of carbon monoxide gas, it is necessary to create a carbon monoxide gas detection tool. The carbon monoxide gas detection tool in motor vehicles uses an MQ-7 sensor. The data obtained from the MQ-7 sensor will be processed by the ESP8266 microcontroller and the results are displayed on the PC via LCD, the application program design uses the C ++ programming language. In the test there are two processes, namely inside the car and outside the car. The lowest carbon monoxide level in the car is 7.23 ppm and the highest is 9.65 ppm. While testing outside the car the lowest carbon content is 96.26 ppm and the highest level is 97.76 ppm..